PENGARUH HARGA DAN KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN MELALUI MINAT BELI KONSUMEN SEBAGAI VARIABEL INTERVENING PADA CAFE ANAK PANTAI DI CERMEE BONDOWOSO - Maydona, Riki; Arief, Muhammad Yahya; Harisandi, Yudhistira (Fakultas Ekonomi dan Bisnis, 2022)
Marketing management can also be interpreted as the art and science of choosing target markets designed to create, build and maintain profitable exchanges to achieve company goals. Therefore, proper marketing management can improve especially in the development of the Anak Pantai Cafe. at Cermee Bondowoso. The purpose of this study was to analyze and examine the effect of price and service quality in determining consumer satisfaction with consumer buying interest as an intervening variable. The population in this study is the Consumers of the Beach Children's Cafe in Cermee Bondowoso. The sampling method is determined by probability sampling. Data analysis and hypothesis testing in this study used the Structural Equation Model – Partial Least Square (PLS-SEM). The results of the direct influence hypothesis test using the Smart PLS 3.0 application, indicate that price has a significant positive effect on consumer buying interest, service quality has a positive but not significant effect on consumer buying interest, price has a significant positive effect on consumer satisfaction, service quality has a significant positive effect on consumer satisfaction, Consumer buying interest has a positive but not significant effect on consumer satisfaction. The results of the indirect influence hypothesis show that the price variable on consumer satisfaction through consumer buying interest has a positive but not significant effect, service quality on consumer satisfaction through consumer buying interest has a positive but not significant effect.